Reflective practice as part of the professional development of nursing students: A Cross-Sectional Study - Iris Ruzzier; Sabina Ličen; Mitja Zdovc; Marko Milačak; Mirko Prosen (Global Nursing Insights, 2026)
Aim: The aim of the study was to quantitatively assess reflective capacity among nursing students and to examine the expression of its dimensions in the clinical learning environment.Material and Methods: A cross-sectional quantitative study design was used. A purposive sample of 177 nursing students enrolled in the Nursing programme in Slovenia participated in the study. Data were collected between October and December 2025 using the Reflective Practice Questionnaire. The study used the 16-item reflective capacity subscale, which includes four dimensions: reflection-in-action, reflection-on-action, reflection with others, and self-appraisal. Data were collected through an anonymous online survey (1KA). Statistical analyses were performed using SPSS 29. Descriptive statistics were calculated, and internal consistency was assessed using Cronbach’s alpha. Due to non-normal data distribution, non-parametric tests were applied, including the Wilcoxon signed-rank test, Friedman test, Mann–Whitney U test, Kruskal–Wallis test, and Spearman’s correlation coefficient.Results: The results showed a relatively high level of reflective capacity among nursing students (Mdn = 4.56). Based on median values, the highest scores were observed in reflection with others and self-appraisal, while the lowest were found for reflection-in-action. Differences between reflective capacity dimensions were not statistically significant (χ²(3) = 2.399, p = 0.494). No significant differences were observed between full-time and part-time students or across years of study (p > 0.05). Age was not significantly associated with reflective capacity, except for a weak negative correlation with reflection with others (ρ = −0.193, p = 0.011). Students who perceived reflection as important for their professional development and those interested in additional practical training demonstrated significantly higher levels of reflective capacity (p < 0.05).Conclusion: The findings indicate that nursing students demonstrate a relatively high level of reflective capacity, particularly in collaborative reflective processes. Reflective practice appears to be an important component of clinical learning and professional development in nursing education.Implication for nursing practice: Structured reflective activities, mentoring conversations, and guided reflection in clinical environments may strengthen students’ clinical judgement, professional responsibility, and quality of patient care.